Surveillance dan Penyebaran Penyakit Tangan, Kaki, dan Mulut (HFMD): Tinjauan Pustaka - Adrian, Reza (Cermin Dunia Kedokteran, 2024)
Hand, foot, and mouth disease (HFMD) is a common viral illness primarily affecting children. HFMD is caused by various types of coxsackievirus and enterovirus; the main causes are coxsackievirus A16 and enterovirus A71. This article discusses HFMD surveillance and its spread in several countries, including China, Singapore, and Indonesia, aiming to understand the surveillance processes and HFMD distribution to formulate effective prevention and management strategies.